Chemical Separation of Compounds from Antituberculosis Drug and Their Antibacterial Biological Activity - Othman Dakhil; Yasmin Yahya; Hanan Abdalkrim; Salwa Eltawaty (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. In this study separated between the active ingredients of the expired isoniazid. The separated substance may enhance antibacterial biological activity. Methods. The target compounds were designed is added to the ketone (acetyl acetone) as the primary amine (isoniazid), the other to the preferred substance (isoniazid) with the aldehyde (benzaldehyde), and the final reaction is the separated substance (isoniazid) with (p-methoxy benzaldehyde) were evaluated for antibacterial biological activity against tested clinical Escherichia coli (E. coli) and Methicillin Resistant Staphylococcus aureus (MRSA)and were subjected to molecular properties and bioactivity prediction by the Molinspiration. Results. The compound (1-isonicotinoyl-3,5-dimethyl-4-H-pyrazol-1-ium) exhibited significant antibacterial activity on tested gram negative and gram-positive bacteria. Furthermore, compounds (E)-N-benzylidene isonicotiolryazide) and (E)-N’-(4-methoxybenzylidene) isonicotinohydrazide showed intermediate inhibitory activity against gram-negative Escherichia coli (E. coli). Furthermore, all compounds obeyed Lipinski’s rule of five. Also, compounds (E)-N-benzylidene isonicotiolryazide) and (E)-N’-(4-methoxybenzylidene) isonicotinohydrazide have drug-like properties within those considered adequate for a drug candidate. Conclusion. separating expired drugs has a helpful effect in discovering drugs.